Motherhood as a Source of Empowerment of Women in Yoruba Culture (Nordic Journal of African Studies, 2004)
The paper looks into Yoruba culture with emphasis on motherhood and how it empowers women in Yorubaland. It also looks at other areas of Yoruba perception of women and how these different perceptions empower women in Yoruba culture. It tries to find ways by which consideration of Yoruba culture as regards women can contribute to the improvement of life for women generally.In order to achieve this objective, the paper looks at the various ways by which Yoruba culture views women - as priestesses, as wives, as daughters, as witches, and, most especially, as mothers. Both the positive and the negative aspects of the culture are discussed. The paper comes up with suggestions on how the conception of motherhood in Yoruba culture can enhance the considerations given to women at the policy formulation stage.